Performance of nickel cobaltite - anodised titania nanotubes composite electrochemical capacitor electrodes in different electrolytes - Chua, Chi Wing; Zainal, Zulkarnain; Lim, Hong Ngee (2017)
The effects of electrolyte on the electrochemical performance of nickel cobaltite – titania nanotubes composite electrochemical capacitors were evaluated. Four types of electrolyte were selected, namely aqueous electrolytes, 1.0 M KCl, 1.0 M HCl, 1.0 M KOH; and organic 0.27 M tetra-n-butylammonium tetrafluoroborate (TBATFB) in acetonitrile. Results have shown optimal performance in 1.0 M KOH, which endowed the composite with excellent rate capability up to 200 mV s-1. Charge – discharge analyses has shown that the composite possessed specific areal capacitance of up to 214 μF cm-2 when evaluated at a current density of 350 μA cm-2. The composite retained up to 97.79 % of its capacitance when current density was increased to 400 μA cm-2. The composite has demonstrated a promising application for electrochemical capacitors through its facile fabrication technique.